Avaliação da biodegradação de hexadecano por um consórcio de actinobactérias imobilizado em quitosana em microcosmos de sedimentos de manguezal por medida de atividade desidrogenásica - Alves, Bella Giselly Torres (2018)
The contamination by oil and its derivatives is a recurrent problem for costal ecosystems, such as mangroves. Among decontamination techniques, bioremediation with immobilized microorganisms stands out because of the protection conferred by the matrix to the degrading microorganisms, besides the easier application, transport and storage. The objective of this study was to analyze the biodegradation of hexadecane in a microcosm of mangrove sediment by a consortium of hydrocarbonoclastic actinobacteria. For that, the consortium composed by Gordonia sp. (Hex 5) and Micrococcus sp. (Hex 6), in free form and immobilized in chitosan spheres, was utilized to degrade hexadecane in a microcosm for 35 days. The biodegradation was monitored by counting of viable cells and measure of dehydrogenase activity (DHA). Furthermore, assays were performed to identify biosurfactants production and the alkB gene, that codes the alkane monooxygenase, a key enzyme to the pollutant degradation. The analysis showed that the group treated with the immobilized consortium presented high ADH (12 ± 0,11 µg TPF g-1 h-1) in the sixth day, along with a spike in the viable cell count (6,4 X 108 CFU/g). The untreated group held the ADH at 0,41 ± 0,05 µg TPF g-1 h-1 and the viable cell count at 3,3 X 107 CFU/g. The group treated only with chitosan presented its highest DHA in the third day, displaying a biostimulant effect of the sediment’s autochthonous microbiome. The free consortium promoted a spike in the ADH and in the viable cell count albeit significantly lower than the immobilized consortium. Both cultures produced biosurfactants and only HEX 5 was detected to have de alkB gene. The product developed in this study represents an inovation for bioremediation of sediments contaminated with alkanes, with the advantage of being eficient, easy to use, transport, store and it is biodegradable and environment friendly.